p PENGARUH DARK HUMOR TERHADAP PERILAKU CYBERBULLYING REMAJA - Syammari, Shoofii; Sari, Nina Permata; Setiawan, Muhammad Andri; Nurrofifah, Hani; Zahidah, Asih Nor (Irfani, 2026)
This study examines the influence of dark humor on cyberbullying behavior among vocational high school (SMK) students. Using a quantitative approach with a simple linear regression design, it involved 88 SMK students selected via total purposive sampling. Data were gathered using the dark humor scale (Cronbach's α = 0.943) and cyberbullying scale (Cronbach's α = 0.867), both tested for validity and reliability. The hypothesis that dark humor positively affects cyberbullying behavior was confirmed, evidenced by the regression equation Y = 27.121 + 0.520X, correlation coefficient R = 0.661, coefficient of determination R² = 0.473 (47.3% contribution), F-value = 66.691 (Sig. = 0.000), and t-value = 8.166 (p < 0,001). Classical assumptions of normality (Kolmogorov-Smirnov Sig. = 0.119) and homoscedasticity were fulfilled. Dark humor significantly and positively influences cyberbullying among SMK students. This research enriches the psychological literature on cyberbullying by highlighting dark humor as a key predictor. The findings support developing school counseling programs to reduce dark humor tendencies and prevent cyberbullying